Substituents effect on corrosion inhibition performance of organic compounds in aggressive ionic solutions: A review - Verma C.; Olasunkanmi L.O.; Ebenso E.E.; Quraishi M.A. (My University, 2025)
One of the factors that limit the use of synthetic organic compounds as corrosion inhibitors is the series of trials associated with traditional syntheses that have to be carried out in the course of designing of new and efficient corrosion inhibitors. A large number of synthetic trials are not only cost-ineffective but also time consuming, which involves too many work-ups and often results in increased discharge of environmentally malignant materials into the surrounding. However, a good understanding of the relationship between molecular and electronic structures of organic molecules and their corrosion inhibition potentials can aid the design of new corrosion inhibitors in great stead. The simplified model for the prediction of relative performances of chemisorbed organic molecules as corrosion inhibitors holds that electron donating substituents promote inhibition effectiveness while electron withdrawing substituents reduce corrosion inhibition potential. Exceptions to this generalization have been found in few published works though. This review article features the collection of observed results and inferences from previous works that investigated the effects of substituent groups on corrosion inhibition properties of organic molecules. © 2017 Elsevier B.V.